Groundwater Pollution Risk Analysis in Wonosari Basin and Gunungsewu Karst Transition Zone, Gunungkidul, Indonesia - Sisthannisa, R. (EDP Sciences, 2023)
The Wonosari Basin and Gunungsewu Karst Transition Zone have enormous hydrological potential, but highly complex human activities put them at risk of groundwater pollution. This research was designed to analyze the distribution of groundwater vulnerability to pollution, potential sources of contamination (i.e., hazards), and groundwater pollution risk in both areas. The COP method was employed to determine the vulnerability, with modifications on the calculation of lithology (OL), a subfactor of overlying layers (O). The hazard and risk assessments were based on the approach developed by COST Action 620. Based on the values, both study areas are dominated by very low to low vulnerability, with higher values in the transition zone than in the basin. Similarly, the groundwater is generally exposed to activities with a low potential for contamination. However, the hazard values were found to be higher in the basin, which can be linked to its more varied, intensive, and complex anthropogenic activities. Further, the distribution pattern showed that the majority of the two areas have low and very low risks of groundwater pollution, with a higher value measured in the transition zone. © 2023 EDP Sciences. All rights reserved.